European neighborhood policy and association agreements: The case of Morocco - Φουτσιτζή, Θεοδώρα (Πανεπιστήμιο Πελοποννήσου, 2019)
ENP was established in 2004 as an instrument of EU’s foreign policy towards bordering states, continuing the approach of Barcelona Process towards the Southern Mediterranean countries and alongside as the framework, on which EU established bilateral agreements with these countries individually. Its declared targets were: the more peace, democracy and economic development can be prevailed, the largest of stability and security can be achieved. But during the 2000’s ENP resulted to failure since EU avoided to be a reliable international player. Despite its ineffectiveness, ENP is still alive today, since it is the framework, upon which association agreements with the Mediterranean countries are based. The next decade the approach of EU is still based on ENP but now it prefers to promote security and political stability rather than democratic reforms, continuing to provide to the authoritarian regimes in the MENA countries either association agreements or financial assistance. This is exactly the case of Morocco. EU prefers to be blindfold about the “democratic reforms” and the real political conditions in Morocco. The point of this thesis, are the constitutional amendments in 2011, which maintained the over-authorities of the king and the illegal annexation of Western Sahara
Η ευρωπαϊκή πολιτική γειτονίας και οι συμφωνίες συνεργασίας: Η περίπτωση του Μαρόκου
Keywords: Μαρόκο--Πολιτική και διακυβέρνηση; Μαρόκο--Εξωτερικές σχέσεις; Μαρόκο--Πολιτικές συνθήκες; Μαρόκο--Κοινωνικές συνθήκες; Ευρωπαϊκή Πολιτική Γειτονίας (ΕΠΓ); Μαρόκο; Συνταγματικές Μεταρρυθμίσεις